Percutaneous Treatment of Left Side Cardiac Valves A Practical Guide for the Interventional Cardiologist (Springer International Publishing, 2018)
After the success of the first two editions, this expanded and extensively revised edition provides the interventional cardiologist with detailed, state of the art information on key techniques and approaches to percutaneous treatment of left side cardiac valve disease, keeping pace with the rapid and dynamic evolution in the discipline. Many new techniques and resources are now available, including new devices for transcatheter aortic valve implantation and new approaches to transcatheter mitral valve replacement. Numerous images will help the reader to understand the steps of each procedure and the characteristics of the different devices available. The potential complications and expected or potential morbidity from each procedure are discussed in depth, along with the best ways to manage them. Transcatheter aortic valve implantation has revolutionized the field of interventional cardiology. Initially envisaged as a palliative technique for inoperable patients, it now offe rs high-risk patients a viable alternative to surgery. Several techniques are also available of transcatheter mitral valve repair, and initial cases of transcatheter mitral valve replacement have also been reported: the interest in these techniques is such that further significant technological advances are expected to be seen over the next few years. This highly informative, easy to read, and carefully structured guide provides interventional cardiologists with updated knowledge on the application of transcatheter techniques to cardiac valves.